2022
DOI: 10.15406/jdhodt.2022.13.00575
|View full text |Cite
|
Sign up to set email alerts
|

Mental foramen as an indicator of patient’s gender, panoramic study in Qassim province, Saudi Arabia

Abstract: Introduction: Gender can be determined by numerous pieces of the skeleton structure. Mental foramen is one of the mandibular components that can demonstrate the gender. Aim of the study: to assess patient’s gender by analysis of mental foramen on panoramic radiograph in Qassim region. Method and material: A retrospective study was performed on 400 panoramic radiographs. 200 males and 200 females were included in this study. Panoramic radiograph machine was used in this study is (Soredex-cranex x- ray machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The distance from the superior border of the mental foramen to the inferior border of the mandible was shown to differ significantly between genders in a study conducted by Sheikhi & Kheir [ 30 ]. Other studies [ 12 , 31 ] also showed that distances from the MF to the alveolar crest and inferior mandibular border were significantly higher for males.…”
Section: Discussionmentioning
confidence: 77%
“…The distance from the superior border of the mental foramen to the inferior border of the mandible was shown to differ significantly between genders in a study conducted by Sheikhi & Kheir [ 30 ]. Other studies [ 12 , 31 ] also showed that distances from the MF to the alveolar crest and inferior mandibular border were significantly higher for males.…”
Section: Discussionmentioning
confidence: 77%